Cerebellar anaplastic astrocytoma in adult patients: 15 consecutive cases from a single institution and literature review. (September 2021) - Belyaev, Artem; Usachev, Dmitry; Ryzhova, Marina; Gulida, Gleb; Skvortsova, Vasilisa; Pronin, Igor; Kobiakov, Grigory
Highlights: Cerebellar anaplastic astrocytomas are extremely rare entities. Incidence of IDH-1 mutation in cAA is higher than in cerebellar glioblastomas. Patients with cAA tend to have a more frequent multifocal presentation at diagnosis. Overall survival rates for patients with cAA was compatible to the control group with supratentorial anaplastic astrocytomas. Abstract: Adult cerebellar anaplastic astrocytomas (cAA) are rare entities and their clinical and genetic appearances are still ill defined. Previously, malignant gliomas of the cerebellum were combined and reviewed together (cAA and cerebellar glioblastomas (cGB), that could have possibly affected overall survival (OS) and progression-free survival (PFS). We present characteristics of 15 adult patients with cAA and compared them to a series of 45 patients with a supratentorial AA (sAA) in order to elicit the effect of tumor location on OS and PFS. The mean age at cAA diagnosis was 39.3 years (range 19–72). A history of neurofibromatosis type I was noted in 1 patient (6.7%). An IDH-1 mutation was identified in 6/15 cases and a methylated MGMT promoter in 5/15 cases. Patients in study and control groups were matched in age, sex and IDH-1 mutation status. Patients in a study group tended to present with longer overall survival (50 vs. 36.5 months), but the difference did not reach statistical significance. In both cAA and supratentorial AA groups presence of the IDH-1 mutation remains a positive predictor for the prolonged survival. The present study suggests that adult cAA constitute a group of gliomas with relatively higher rate of IDH-1 mutations and prognosis similar to supratentorial AA. The present study is the first to systematically compare cAA and supratentorial AA with respect to their genetic characteristics and suggests that both groups show a similar survival prognosis.